The study of fluid inclusions and genesis of mineralization in the northwest of Gonabad, the Southern Khorasan Razavi province - Sedigheh Zirjanizadeh; Mohmmad Hassan Karimpour; Somayeh Samiee; Azam Entezari Hersini (Journal of Economic Geology, 2020)
Introduction The study area is located in the Khorasan Razavi Province, NW of Gonabad between 58° 33˝- 58 ° 38˝ to the east and 25° 34˝ - 25° 38˝ to the north. Geotectonically, the area is located in the northern part of the Lut Block. The Lut Block is the main metallogenic province in the east of Iran (Karimpour et al., 2012). There is a significant outcrop of Tertiary intermediate volcanic and pyroclastic rocks in the northwest of Gonabad. This region is rich in clay (kaolin) mineralization. The source of these kaolin deposits (argillic alteration) is related to a granitic dyke that intruded into the Shemshak Formation.